2019
DOI: 10.1002/anie.201913003
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Electrosynthesis of Syngas with Tunable CO/H2Ratios over ZnxCd1−xS‐Amine Inorganic–Organic Hybrids

Abstract: Efficient electrochemical reduction of CO2 and H2O into industrial syngas with tunable CO/H2 ratios, especially integrated with anodic organic synthesis to replace the low‐value oxygen evolution reaction (OER), is highly desirable. Here, integration of controllable partial substitution of zinc (Zn) with amine incorporation into CdS‐amine inorganic‐organic hybrids is used to generate highly efficient electrocatalysts for synthesizing syngas with tunable CO/H2 ratios (0–19.7), which are important feedstocks for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…To get fundamental insight into the intrinsic activity, the electrochemical active surface areas (ECSA) of those polymers were assessed by measuring the electrochemical layer capacitance (C dl ) due to their positive proportion relationship (Figure S27, Supporting Information). [44,45] As depicted in Figure 3e, the ECSA (37.8 cm 2 ) of metal-free H 2 Por-N 3 is much smaller than that of CuPor-N 3 (42.8 cm 2 ), H 2 Por-RuN 3 (75.0 cm 2 ) and CuPor-RuN 3 (72.2 cm 2 ), demonstrating that the introduction of metal centers is beneficial for exposing more active sites. From the LSV curves (Figure 3f) after being ECSA-normalized, it can be found that CuPor-RuN 3 still shows an intrinsic electrocatalytic activity superior to H 2 Por-N 3 , CuPor-N 3 and H 2 Por-RuN 3 , demonstrating that the Cu/Ru hetero-bimetallic centers induce the well-suited electronic structure and improve the reactivity of single-atom active sites.…”
Section: Resultsmentioning
confidence: 95%
“…To get fundamental insight into the intrinsic activity, the electrochemical active surface areas (ECSA) of those polymers were assessed by measuring the electrochemical layer capacitance (C dl ) due to their positive proportion relationship (Figure S27, Supporting Information). [44,45] As depicted in Figure 3e, the ECSA (37.8 cm 2 ) of metal-free H 2 Por-N 3 is much smaller than that of CuPor-N 3 (42.8 cm 2 ), H 2 Por-RuN 3 (75.0 cm 2 ) and CuPor-RuN 3 (72.2 cm 2 ), demonstrating that the introduction of metal centers is beneficial for exposing more active sites. From the LSV curves (Figure 3f) after being ECSA-normalized, it can be found that CuPor-RuN 3 still shows an intrinsic electrocatalytic activity superior to H 2 Por-N 3 , CuPor-N 3 and H 2 Por-RuN 3 , demonstrating that the Cu/Ru hetero-bimetallic centers induce the well-suited electronic structure and improve the reactivity of single-atom active sites.…”
Section: Resultsmentioning
confidence: 95%
“…Syngas, composedo fH 2 and CO, is as ignificant feedstock for production of high-valued longerh ydrocarbons through wellestablished processes, such as the Fischer-Tropsch (F-T) process and syngas fermentation. [1,2] CO 2 photoreduction driven by sunlight not only provides an alternate approach for the generation of useful chemicals (e.g.,s yngas) in an environmentally friendly, [3][4][5] sustainable, and low-cost way but also alleviates the environmental burden caused by excessive CO 2 emissions. Numerous photocatalysts with high activity have been developedf or CO 2 reduction to syngas, but they usually use pure CO 2 ,w hich needs to be extracted from the atmosphere first.…”
Section: Introductionmentioning
confidence: 99%
“…The band at 1635 cm −1 is attributed to interfacial water [44]. While the band at 1400 cm −1 represents the absorption of *COOH [45,46], indicating the formation of CO is with *COOH as the intermediate. The *COOH intensity of pCNTA10 is slightly stronger than that of CNTA, reflecting that the plasma treatment is beneficial to the selectivity to CO.…”
Section: Plasma-regulated N-doped Carbon Nanotube Arrays For Efficienmentioning
confidence: 99%